Study of a-Plane GaN Epitaxial Lateral Overgrowth Using Carbonized Photoresist Mask on r-Plane Sapphire - Jang, Samseok; Lee, Dohan; Kwon, Jun-hyuck; Kim, Sang-il; Yim, So Young; Lee, Jaesang; Park, Ji Hun; Byun, Dongjin (IOP PUBLISHING LTD, 2012)
Epitaxial lateral overgrowth (ELO) a-plane GaN samples were successfully grown on masked sapphire (1 (1) over bar 02) substrates using an in-situ carbonized photoresist (PR) mask by a metalorganic chemical vapor deposition (MOCVD) method. The PR masks for the ELO process were prepared using conventional lithography in the form of a stripe with an opening of 4 mu m and a period of 12 mu m. The stripe-patterned PR was annealed at 1100 degrees C in a H-2 atmosphere. The stripes were aligned parallel to the (1 (1) over bar 00)(GaN) direction. The ELO process of GaN was strongly dependent on the direction of the stripes. Overall, the PR masks on the r-plane sapphire substrate were carbonized during the heating step before the main growth, so that the carbonized PR mask acted as an ELO mask. The study results confirmed the promising potential of the ELO process using an in-situ carbonized PR mask on r-plane sapphire. (C) 2012 The Japan Society of Applied Physics
Keywords: VAPOR-PHASE EPITAXY; LAYERS; REDUCTION; TEMPLATES; SUBSTRATE; DENSITY; GROWTH